Differentiate and equate to zero
Hence
y = x^2 + 4x - 12
dy/dx = 2x + 4 = 0
2x = -4
x = -2
Hence
y = (-2)^2 +4(-2) - 12
y = 4 - 8 - 12
y = - 16
Hence the vertex is (x,y,) = ( -2,-16)
Y = X2 - 4X + 12
set to 0
X2 - 4X + 12 = 0
subtract 12 from each side
X2 - 4X = - 12
now, take the linear term ( - 4 ), halve it, square it and add it to both sides
X2 - 4X + 4 = - 12 + 4
factor the left side, gather terms on the right
(X - 2)2 = - 8
add 8 to each side
(X - 2)2 + 8 = 0
------------------------
(2, 8)
------------the vertex of this function